Zambia [in Strategies and priorities for African agriculture] - Thurlow, James; Benin, Samuel; Diao, Xinshen; Kalinda, Henrietta; Kalinda, Thomson (International Food Policy Research Institute, 2012)
Zambia was classified as a middle-income country after it gained independence in the 1960s. However, the economy deteriorated into low-income status over the next two decades, culminating in a major macroeconomic crisis in the late 1980s (World Bank 2010). The 1990s marked the advent of painful structural reforms, during which the state’s ubiquitous interventions were removed and markets were liberalized. Comprehensive agricultural reforms entailed the removal of food and input subsidies and pan-territorial maize pricing (McCulloch, Baulch, and Cherel-Robson 2001). In many parts of the country these reforms led to a reallocation of productive resources away from maize and to more naturally suitable crops (for example, cassava in Northern Province) (Zulu et al. 2000). Eventually, liberalization encouraged the emergence of new export crops, such as cotton, which is now grown by one-fifth of all farm households (Jayne et al. 2007) and is credited with having reduced poverty in Eastern Province (see McCulloch et al. 2001). However, the reforms were not universally beneficial and did not address all constraints facing smallholders (Seshamani 1999).